FUNGSI KERAMIK CINA BAGI MASYARAKAT BIAK - Maryone, Rini (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2009)
The presence of foreign-made ceramics in Papua, especially in Biak Island, has shown that historically before the 15th century Papua has made contact with foreign countries, such as the merchants from China, Spain and Portugal. The name Nova Guinea given to Irian by the sailor from Spain is also shown that this land has made contact with foreigners. Other than foreign influence, it is admitted that the Biak community has sailed a long way to the west of Maluku, Tidore and Halmahera. They’re known as excellent seamen who sailed across the vast ocean from North-Coast of Papua to the Bird’s Head Peninsula and Raja Ampat Islands. On their way back home, most of the time they brought back the foreign-made ceramics or as the Biak community said “benbepon” and textile “sananpun”. As a result, their contact with foreign countries has made changes in material life of Biak community.